The effects of non-uniformly-aged photovoltaic array on mismatch power loss : A practical investigation towards novel hybrid array conﬁgurations - Al Mansur, Ahmed; Amin, Md Ruhul; Hossain Lipu, Molla Shahadat; Islam, Md Imamul; Ashique, Ratil H.; Shams, Zubaeer; Haq, Mohammad Asif ul; Maruf, Md Hasan; Shihavuddin, Asm S.M. (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
One of the most important causes of a reduction in power generation in PV panels is the non-uniform aging of photovoltaic (PV) modules. The increase in the current–voltage (I–V) mismatch among the array modules is the primary cause of this kind of degradation. There have been several array configurations investigated over the years to reduce mismatch power loss (MPL) caused by shadowing, but there have not been any experimental studies that have specifically examined the impact of various hybrid array topologies taking PV module aging into consideration. This research examines the influence of the non-uniform aging scenario on the performance of solar PV modules with various interconnection strategies. Experiments have been carried out on a 4 × 10, 400 W array with 12 possible configurations, including three proposed configurations (LD-TCT, SP-LD, and LD-SP), to detect the electrical characteristics of a PV system. Finally, the performances of different module configurations are analyzed where the newly proposed configurations (SP-LD and LD-SP) show 15.80% and 15.94% higher recoverable energy (RE), respectively, than the most-adopted configuration (SP). Moreover, among the twelve configurations, the SP configuration shows the highest percentage of MPL, which is about 17.96%, whereas LD-SP shows the lowest MPL at about 4.88%.